(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the effectiveness of multisensory teaching methods in primary education through a case study of one school in Uzbekistan. Multisensory teaching engages visual, auditory, and kinesthetic channels simultaneously. The study observed 42 first-grade students over eight weeks. Data were collected through classroom observations, teacher interviews, and analysis of student work. Results indicate increased student engagement, improved retention of basic concepts, and higher participation compared to traditional lessons. Low-performing students benefited most. Teachers noted challenges including preparation time and classroom noise, but confirmed willingness to continue using multisensory methods. The study concludes that multisensory approaches can be effectively implemented in Uzbek primary schools with minimal resources. Limitations include small sample size and short duration.